A importância do marketing na conquista e fidelização de clientes de shopping center - Eberius, Maria Luiza (2002)
Shopping center is a very competitive market and marketing management requires certain tools to deal with, as well as complying with a specific profile and characteristics expected from him. This study was based in both theoreticaI and practicaI perspectives. A counterpoint between theme references and exploratory research was established through personal interviews with top management oflocaI shopping centers, selected in the Rio de Janeiro area. Themes such as Administration and Marketing were discussed, being Marketing Plan and Research specially cited as the main working tools for a shopping center marketing management. In the course of these interviews, certain topics were projected, such as personal experiences in retailing, suitable characteristics required for a marketing manager, adequate marketing tools and even the significance of a competitive positioning regarding both audience's point ofview about shopping center. Both audiences pointed out how important is marketing within a business management context, and how a good marketing performance is related to customer's 10yaIty. Such performance leads the way to a definition in the shopping's image and for that, each and every staff member must be committed to. Shopping centers mean more than just a place where people go for buying, it is a place where most of their dreams come true, and the marketing manager, by using of the pro per promotional marketing procedures, along with his own technicaI abilities, must optimize this and carry it out.